Autophagy-Induced HDAC6 Activity During Hypoxia Regulates Mitochondrial Energy Metabolism Through the β-Catenin/COUP-TFII Axis in Hepatocellular Carcinoma Cells - Yan, Xiaoyu; Qu, Xianzhi; Liu, Buhan; Zhao, Yuanxin; Xu, Long; Yu, Sihang; Wang, Jian; Wang, Liying; Su, Jing (Frontiers in Oncology, 2021)
Hypoxia is one of the main driving forces that results in poor outcomes and drug resistance in hepatocellular carcinoma (HCC). As the critical cellular oxygen sensor, mitochondria respond to hypoxic stress by sending retrograde signals to the nucleus that initiate adaptive metabolic responses and maintain the survival of HCC cells. Increasing evidence suggested autophagy contributes to sustain mitochondrial metabolic and quality control. Understanding how mitochondria communicate with the nucleus and alter transcription may provide promising targets for HCC treatment. In this study, we found mitochondrial undergo selective degradation by autophagy under hypoxia. Furthermore, autophagy-activated HDAC6 not only promoted the nuclear translocation of β-catenin but also increased the affinity of β-catenin to the transcription repressor chicken ovalbumin upstream promoter-transcription factor 2 (COUP-TF Ⅱ), which suppressed mitochondrial oxidative phosphorylation-related genes transcription. Our data show that autophagy served as a critical mediator of integrating mitochondrial energy metabolism and nuclear transcription. HDAC6 may be a potential target for reducing the survival of HCC cells by interrupting mitochondrial–nuclear crosstalk.